Psychosemantic Approach as the Basis of Algorithmization of Students' Work with Vocation-Oriented Information - Bystrenina, Irina (2021)
The article substantiates the need to create a technology for algorithmic work with professionally oriented information of a textual nature, based on the principles of the psychosemantic approach, which make it possible to most effectively define and logically form the semantic components of external speech and thinking. The authors of the article apply the original methodological concept of the characteristics of textual information, which is considered as a mechanism of learning and professional communication. Algorithmization of the process of mastering information will speed up the learning process and master a large amount of complex professional information. The algorithms proposed in the described technology have the property of modifiability and can be applied by students in their further studies and professional activities in a wide range of information interaction situations.